Dinamika Islam Singapura: Menelisik Pengalaman Minoritas Muslim di Negara Singapura yang Sekular & Multikultural - Helmiati Helmiati (Lembaga penelitian dan pengabdian kepada masyrakat, 2013)
This article tries to study about how Muslim minority of Singapore have reconciled Islamic teachings with the unique challenges of their days. As we know, they live in a plural society, secular state, and globalised modern world. There are many challenges. Nevertheless, their experiences show how they practise Islam with relative ease; how they seek to harmonise religious teachings with their unique circumtances succesfully; and how they take care of the Islamic civilization well. Indeed, the external factors, such as the geopolitical situation and practice Islam. However, It shows that Islam remains compatible with any condition, including with the process of modernisation as long as the practice of the religion remains guided by its fundamental principles. Even, in the context of modernisation, Islam plays it’s role as spiritual bodyguard toward the bitterness of development. Further, Muslim Minority of Singapore’s experiences strengthen Gellner’s statement that “Islam is the great exception to secularization”.